Lateral Medullary Syndrome Following Varicella - J Gordon Millichap (Pediatric Neurology Briefs)
The acute onset of lateral medullary (Wallenberg’s) syndrome in a 6-year-old boy 32 days after varicella infection is reported from the Children’s Hospital, Harvard Med Sch, Boston.